2014
DOI: 10.1080/15381501.2013.864175
|View full text |Cite
|
Sign up to set email alerts
|

Presence of an HIV Testing Program Lowers the Prevalence of Unprotected Insertive Anal Intercourse Inside a Gay Bathhouse Among HIV-Negative and HIV-Unknown Patrons

Abstract: This study sought to determine whether the presence of HIV testing inside a gay bathhouse reduced sexual risk behavior among patrons. A two-stage, time probability, cluster sample design recruited men exiting a northern California bathhouse in the last 5 weeks of 2001 (N=440), when no HIV testing was offered inside the bathhouse, and again in the last 5 weeks of 2002 (N=412) when HIV testing was offered 5 days a week. Separate logistic regression analyses compared a 2002 HIV testing exposure subgroup to both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The 41% response rate is lower than what we obtained at a different bathhouse at the beginning of the decade (Woods et al, 2007; Pollack et al, in press), but it is similar to the 45% rate reported by Grov (2012) for a recent time-location sample survey of New York City bathhouses. It is important to remember that response rate is only a weak indicator of response bias, i.e., a low response rate does not guarantee high levels of bias and a high response rate does not obviate response bias (Groves, 2006; Reidy et al, 2009).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The 41% response rate is lower than what we obtained at a different bathhouse at the beginning of the decade (Woods et al, 2007; Pollack et al, in press), but it is similar to the 45% rate reported by Grov (2012) for a recent time-location sample survey of New York City bathhouses. It is important to remember that response rate is only a weak indicator of response bias, i.e., a low response rate does not guarantee high levels of bias and a high response rate does not obviate response bias (Groves, 2006; Reidy et al, 2009).…”
Section: Discussionsupporting
confidence: 64%
“…Bathhouses already serve as sites for some individual-level interventions primarily in the form of education and condom distribution (Woods, Euren, Pollack, & Binson, 2010) as well as voluntary counseling and testing (Daskalakis et al, 2009; Huebner et al, 2006). However, greater consideration of the social climate of bathhouses (Binson & Woods, 2003) suggests that larger scale group-level or facility-wide interventions are also possible (see, for example, Pollack, Woods, Blair, & Binson, in press). …”
Section: Discussionmentioning
confidence: 99%
“…Augmenting environments of risk to provide onsite HIV testing services has been shown to reduce sexual risk-taking [44], demonstrating how changes in one’s sexual venue can have important impacts on behavior. Interventions designed to intercede at the times and locations of greatest risk (i.e., that take place using mobile technology accessible anywhere, or interventions designed to occur within [or recruit from] high-risk sexual venues) may, thus, be particularly efficacious among MSM populations and should be patterned to appeal to MSM subpopulation(s) most likely to attend such venues (e.g., materials using gay-centric images and words for CSVs, more neutral imagery for PSEs).…”
Section: Discussionmentioning
confidence: 99%
“…In their evaluation study, Ko et al (2009) found that a structural intervention to increase condom use for anal sex among gay men was successful in producing this effect at the 6-month followup. In recent years, there has been an increase in HIV testing in gay saunas in the US where approximately 75% of the saunas provide this service (Pollack et al, 2014). In several studies, researchers have found high acceptability and effectiveness of HIV self-testing in gay saunas although they do acknowledge the need to ascertain the best way of implementing this service within the sauna (Huebner, Binson, Pollack, & Woods, 2012;Woods, Lippman, Agnew, Carroll, & Binson, 2016).…”
Section: Hiv Risk and Prevention In The Gay Saunamentioning
confidence: 99%
“…The sexual health of sauna users has been a significant focus of both researchers and commentators (e.g., Debattista, 2015;Pollack, Woods, Blair, & Binson, 2014). In Western, industrialized societies, gay men are at disproportionately high risk of HIV and other sexually transmitted infections (STIs) (Jaspal, 2018a).…”
Section: Introductionmentioning
confidence: 99%